Humor, Symbols, and Power: Prabowo-Gibran Political Memes on Social Media in the 2024 Presidential Election - Radians Krisna Febriandy; Tiara Maulinda Habibah; Edison Bonartua Hutapea (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
This research explores the role of political memes in building the image and influencing public perception of the candidate pair Prabowo Subianto and Gibran Rakabuming Raka during the 2024 presidential election campaign. Using the symbolic interaction theory approach and qualitative content analysis, this study analyzed the visual and verbal symbols in memes circulating on social media such as TikTok, Twitter (X), and Instagram. The results show that political memes not only serve as a means of entertainment, but also become an effective communication tool in conveying complex political messages in a way that is easily accepted by the audience. Memes depicting Prabowo as a strong and decisive leader and Gibran as a young innovator create a narrative that reinforces their image as a representation of a blend of experience and innovation. In addition, memes also play a role in increasing political participation among young voters through humor and emotional engagement. This research concludes that political memes play an important role in political contestation in the digital age, facilitating social interaction and shaping political narratives that have a significant impact on public perception and participation.